Lithium battery diaphragm and preparation method thereof

By grafting the activated carbon of soybean meal and combining it with acrylate copolymer and dispersant, a modified separator is formed, which solves the problem of insufficient ion conductivity and liquid absorption retention rate of the lithium battery separator, and significantly improves the Battery performance and safety.

CN119481567APending Publication Date: 2025-02-18HEBEI GELLEC NEW ENERGY MATERIAL SCI&TECHNOLOY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411683102.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The ionic conductivity and liquid retention rate of existing lithium battery separators are insufficient, which affects the energy density and power performance of the battery.

Method used

Modified soybean meal activated carbon is used to modify the soybean meal activated carbon by aqueous polyacrylamide solution at room temperature, so that polar groups are grafted on the surface, combined with acrylate copolymer and dispersant, forming a coating and improving the ions of the separator Conductivity and liquid retention rate.

Benefits of technology

It improves the ionic conductivity and liquid retention rate of the lithium battery separator, enhances the transmission efficiency of lithium ions, reduces internal resistance and breakdown risks, and improves the performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481567A_ABST
    Figure CN119481567A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium battery diaphragm and a preparation method thereof, the lithium battery diaphragm comprises a base membrane and a coating on the base membrane, the coating comprises modified soybean meal activated carbon, an acrylate copolymer and a dispersant, a method for obtaining the modified soybean meal activated carbon comprises the following step: carrying out normal-temperature liquid phase modification on the soybean meal activated carbon by adopting a polyacrylamide-containing solution so as to graft polar groups on the surface of the soybean meal activated carbon, wherein the soybean meal activated carbon is carbonized soybean meal. And the modified soybean meal active carbon is beneficial to enhancing the liquid absorption, liquid retention and wettability of the diaphragm and ensuring more effective transmission of lithium ions, so that the performance of the lithium battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a lithium battery separator and a preparation method thereof. Background Art

[0002] Lithium battery separator is a key component in the battery. It not only provides physical isolation to prevent the positive and negative electrodes from directly contacting each other and causing a short circuit, but also allows lithium ions to pass through to complete the charging and discharging process. The ionic conductivity and liquid absorption and retention rate of the separator directly affect the internal resistance and charging and discharging rate of the battery, which in turn affects the energy density and power performance of the battery. Therefore, improving the ionic conductivity and liquid absorption and retention rate of the separator is an important way to improve the performance of lithium batteries. Improving the ionic conductivity of lithium battery separators is an active research field that aims to promote the improvement of lithium battery performance through advances in materials science and engineering technology, and to meet the needs of modern electronic devices for high energy density and fast charging and discharging.

[0003] Then how to efficiently improve the ionic conductivity and liquid absorption and retention rate of lithium battery separators will become an issue that deserves our attention. Summary of the invention

[0004] In view of the deficiencies of the prior art, an object of the present invention is to provide a lithium battery separator.

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned lithium battery separator.

[0006] Another object of the present invention is to provide a slurry.

[0007] The purpose of the present invention is achieved through the following technical solutions.

[0008] A lithium battery separator comprises: a base film and a coating on the base film, wherein the coating comprises: modified soybean meal activated carbon, an acrylate copolymer and a dispersant, wherein the ratio of the modified soybean meal activated carbon, the acrylate copolymer and the dispersant is (30-40):(5-8):(0.2-0.5) by weight, and the modified soybean meal activated carbon is soybean meal activated carbon with polar groups grafted on the surface, and the polar groups are amino groups.

[0009] In the above technical solution, the ratio of modified soybean meal activated carbon, acrylic ester copolymer and dispersant is (32-40): (5-8): (0.2-0.5) by mass, preferably (32-36): (5-8): (0.2-0.5).

[0010] In the above technical scheme, the method for obtaining the modified soybean meal activated carbon is: using a solution containing polyacrylamide to perform liquid phase modification on the soybean meal activated carbon at room temperature so that polar groups are grafted onto the surface of the soybean meal activated carbon, and the soybean meal activated carbon is carbonized soybean meal.

[0011] In the above technical solution, the dispersant is ammonium polyacrylate.

[0012] In the above technical solution, the particle size of the modified soybean meal activated carbon is: D50 = 0.2-0.3 μm, D90 = 0.5-0.8 μm, the porosity of the modified soybean meal activated carbon is 47-58%, and the specific surface area of ​​the modified soybean meal activated carbon is 2063-2400 m 2 / g.

[0013] In the above technical solution, the specific surface area of ​​soybean meal activated carbon is 1819~2020m 2 / g.

[0014] In the above technical scheme, the method for obtaining modified soybean meal activated carbon is: at room temperature, the soybean meal activated carbon is immersed in a polyacrylamide aqueous solution for at least 30 minutes, dried, and ground to obtain modified soybean meal activated carbon, wherein the concentration of polyacrylamide in the polyacrylamide aqueous solution is 5-10wt%.

[0015] In the above technical solution, the ratio of soybean meal activated carbon to polyacrylamide aqueous solution is (20-30): (70-80) by mass.

[0016] In the method for obtaining modified soybean meal activated carbon, when the soybean meal activated carbon is immersed in a polyacrylamide aqueous solution, it is stirred and ultrasonicated for 30 to 40 minutes in a vacuum environment until it is uniform, wherein the ultrasonic frequency of the ultrasound is 5 to 8 kHz, the vacuum pressure is 0.06 to 0.08 KPA, the stirring rotation speed is 1200 to 4000 r / min, and the revolution speed is 40 to 50 r / min.

[0017] In the above technical scheme, the method for obtaining soybean meal activated carbon includes: carbonizing dried soybean meal at 500-600°C for 2-3 hours under nitrogen or inert gas atmosphere to obtain a first substance, mixing the first substance with an alkaline substance, grinding until uniform, to obtain a second substance, keeping the second substance at 700-800°C for 2-3 hours under nitrogen or inert gas atmosphere, cooling to room temperature, to obtain a third substance, soaking the third substance in an acidic solution to remove surface impurities and the alkaline substance, washing to neutrality, and drying to obtain soybean meal activated carbon, wherein, by mass, the ratio of the first substance to the alkaline substance is (20-30): (70-80).

[0018] In the above technical solution, the specific surface area of ​​soybean meal is 1 to 5 m 2 / g.

[0019] In the above technical solution, the soybean meal is dried at 60-70° C. for 2-3 hours to obtain the dried soybean meal.

[0020] In the above technical solution, the alkaline substance is potassium hydroxide (KOH).

[0021] In the above technical solution, the acidic solution is hydrochloric acid, and the concentration of HCl in the hydrochloric acid is 10 to 15 mol / L.

[0022] The preparation method of the above-mentioned lithium battery separator includes: coating the slurry on the base film, drying, obtaining a coating on the base film, and obtaining the lithium battery separator. The slurry includes: modified soybean meal activated carbon, acrylate copolymer and dispersant.

[0023] In the above technical solution, the coating speed is 20 to 30 m / min.

[0024] In the above technical solution, the coating thickness is 3 to 4 μm.

[0025] A slurry comprises: modified soybean meal activated carbon, water, an adhesive and a dispersant, wherein the adhesive is an acrylate copolymer solution, and the ratio of the modified soybean meal activated carbon, the water, the acrylate copolymer in the adhesive and the dispersant is (30-40): (60-70): (5-8): (0.2-0.5) by weight.

[0026] In the above technical scheme, the ratio of modified soybean meal activated carbon, the water, the acrylic ester copolymer in the adhesive and the dispersant is (32-40): (60-65): (5-8): (0.2-0.5) by mass, preferably (32-36): (60-65): (5-8): (0.2-0.5).

[0027] In the above technical solution, the content of the acrylate copolymer in the acrylate copolymer solution is 20 to 40 wt %.

[0028] The method for preparing the slurry comprises: mixing modified soybean meal activated carbon, water, an adhesive and a dispersant until they are uniform to obtain the slurry.

[0029] The method for preparing the above slurry is specifically as follows: modifying soybean meal activated carbon, water and a dispersant are mixed, and stirred until uniform to obtain a first solution; and the first solution and an adhesive are mixed until uniform to obtain a slurry.

[0030] In the above technical solution, the modified soybean meal activated carbon, water and dispersant are mixed, and stirred at a rotation speed of 2000-3000 r / min and a revolution speed of 40-60 r / min for 20-40 minutes until uniform, to obtain a first solution.

[0031] In the above technical scheme, the first solution and the adhesive are mixed, stirred and ultrasonicated for 20 to 40 minutes in a vacuum environment until they are uniform to obtain a slurry, wherein the ultrasonic frequency of the ultrasound is 5 to 8 kHz, the vacuum pressure is 0.06 to 0.08 KPA, the stirring rotation speed is 2000 to 4000 r / min, and the revolution speed is 40 to 60 r / min.

[0032] Application of polyacrylamide and soybean meal activated carbon in synergistically improving the ionic conductivity and / or breakdown voltage of separators.

[0033] Application of polyacrylamide and soybean meal activated carbon to synergistically improve the liquid absorption rate and / or liquid retention rate of diaphragms.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. High-specific-surface-area soybean meal activated carbon can be obtained by high-temperature carbonization and activation of soybean meal, and the soybean meal activated carbon with high specific-surface-area is modified at room temperature using polyacrylamide (PAM) aqueous solution to graft amino groups on the surface of soybean meal activated carbon. The porosity of soybean meal activated carbon is much greater than that of traditional ceramic materials, which helps to enhance the liquid absorption, liquid retention and wettability of the diaphragm, ensure more effective transmission of lithium ions, and thus improve the performance of lithium batteries. In addition, a large number of polar groups are grafted on the surface of the modified soybean meal activated carbon, which can react with Li + Form coordination bonds and build Li + channels, which help Li + transmission, reducing Li + The migration resistance of lithium ions is reduced, thereby improving the ionic conductivity of the lithium battery separator. The higher specific surface area of ​​modified soybean meal activated carbon helps to disperse the heat inside the battery and reduce the risk of membrane breakdown caused by temperature increase. At the same time, modified soybean meal activated carbon can effectively prevent sharp substances such as lithium dendrites from penetrating the separator and causing short circuits.

[0036] 2. The soybean meal of the present invention is derived from renewable biomass resources, which helps to reduce dependence on fossil fuels and is in line with the trend of sustainable development. Biomass raw materials are usually low in cost, and the present invention reduces production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the SEM of the lithium battery separator prepared in Example 4;

[0038] Figure 2 This is the SEM of the lithium battery separator prepared in Comparative Example 3. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0040] Acrylate copolymer solution: Baoding Lucky Imaging Material Technology Co., Ltd.

[0041] In the following examples, the base film is a PE film, and the thickness of the PE film is 9 μm.

[0042] Ionic conductivity: The test temperature is 25°C and the test relative humidity is 55-60%.

[0043] High ionic conductivity: A high ionic conductivity separator allows lithium ions to pass faster, thereby increasing the battery's charge and discharge rate. Fast lithium ion transmission helps reduce the battery's energy loss during the charge and discharge process, thereby maintaining a higher capacity after multiple cycles. A high ionic conductivity separator also helps reduce the internal resistance of the battery and reduces safety risks caused by internal overheating.

[0044] High liquid absorption and retention rate: High liquid absorption and retention rate ensures that the diaphragm can absorb more electrolyte, which helps to maintain the wet state of the battery during the charge and discharge process, reduce the consumption of electrolyte, and thus improve the cycle life of the battery. Secondly, good liquid retention performance means that the diaphragm can still retain sufficient electrolyte even during battery operation or after long-term storage, which is crucial to maintaining the stability and reliability of the battery.

[0045] Examples 1 to 3

[0046] A method for preparing a slurry comprises: mixing modified soybean meal activated carbon, pure water and a dispersant, stirring the mixture in a double planetary mixer at a rotation speed of R1 r / min and a revolution speed of R2 r / min for B min until the mixture is uniform, obtaining a first solution, mixing the first solution and an adhesive, stirring and ultrasonicating the mixture in a double planetary mixer having an ultrasonic oscillation function under a vacuum environment for C min until the mixture is uniform (the ultrasonic frequency of the ultrasonic wave is 5 kHz, the vacuum pressure is 0.06 KPA, the rotation speed of the stirring is R3 r / min, and the revolution speed is R4 r / min), obtaining a slurry, wherein the adhesive is an acrylate copolymer solution, and the ratio of the modified soybean meal activated carbon, the pure water and the acrylate copolymer to the dispersant in the adhesive is A in terms of mass fraction, the content of the acrylate copolymer in the acrylate copolymer solution is 20 wt% (the acrylate copolymer is polymerized from acrylic acid and acrylamide), and the dispersant is ammonium polyacrylate.

[0047] The method for obtaining modified soybean meal activated carbon (the modified soybean meal activated carbon used in Examples 1 to 3 was obtained from three experiments respectively) is as follows: immersing the soybean meal activated carbon in a polyacrylamide aqueous solution (the ratio of the soybean meal activated carbon to the polyacrylamide aqueous solution is 20:80 by mass), stirring and ultrasonicating for 30 minutes in a double planetary mixer having an ultrasonic oscillation function in a vacuum environment until uniform (the ultrasonic frequency of the ultrasound is 5kHz, the vacuum pressure is 0.06KPA, the stirring rotation speed is R5 r / min, and the revolution speed is 40r / min), drying at 60°C for 2h, grinding, and obtaining the modified soybean meal activated carbon of Examples 1 to 3 respectively, wherein the concentration of polyacrylamide in the polyacrylamide aqueous solution is 10wt%, wherein the method for obtaining soybean meal activated carbon comprises: soaking soybean meal (with a specific surface area of ​​5m 2 / g) was dried at 60℃ for 2h to obtain dried soybean meal, the dried soybean meal was transferred to a quartz tube furnace, carbonized at 500℃ for 2h under argon atmosphere (heated to 500℃ at a rate of 15℃ / min) to obtain a first substance, the first substance was mixed with an alkaline substance (potassium hydroxide) (activation treatment), ground until uniform, to obtain a second substance, the second substance was placed in a quartz tube furnace, kept at 800℃ for 2h under argon atmosphere (heated to 800℃ at a rate of 10℃ / min), cooled to room temperature, to obtain a third substance, the third substance was immersed in an excess of an acidic solution (the acidic solution was hydrochloric acid, and the concentration of HCl in the hydrochloric acid was 10mol / L) to remove impurities and alkaline substances, washed with deionized water to neutrality, and dried at 60℃ for 2h to obtain soybean meal activated carbon (specific surface area of ​​1922m 2 / g), wherein the ratio of the first substance to the alkaline substance is 25:75 by mass.

[0048] A, B, C, R1, R2, R3, R4 and R5 are shown in Table 1.

[0049] Table 1

[0050]

[0051] The particle size of the modified soybean meal activated carbon prepared in Example 1 is D50=0.224 μm; D90=0.654 μm, the porosity is 49.3%, and the specific surface area is 2175 m 2 / g; the particle size of the modified soybean meal activated carbon prepared in Example 2 is D50 = 0.212 μm; D90 = 0.573, the porosity is 48.5%, and the specific surface area is 2203 m 2 / g; The particle size of the modified soybean meal activated carbon prepared in Example 3 is D50 = 0.266 μm; D90 = 0.582 μm, the porosity is 49.1%, and the specific surface area is 2095 m 2 / g.

[0052] Comparative Example 1

[0053] A method for preparing a slurry comprises: mixing aluminum oxide, pure water and a dispersant, stirring in a double planetary mixer for 30 minutes (rotation speed is 3000 r / min, revolution speed is 50 r / min), then ultrasonically treating at a frequency of 5 kHz for 15 minutes, adding an adhesive, and simultaneously ultrasonically oscillating for 20 minutes under stirring conditions (stirring rotation speed is 2000 r / min, revolution speed is 50 r / min, and ultrasonic oscillation frequency is 5 kHz) to obtain a slurry, wherein the adhesive is an acrylate copolymer solution, and the ratio of aluminum oxide, pure water, dispersant and acrylate copolymer in the adhesive is 35:58.5:0.5:6 by weight, wherein the content of acrylate copolymer in the acrylate copolymer solution is 20wt% (acrylate copolymer is polymerized from acrylic acid and acrylamide), the dispersant is ammonium polyacrylate, and the particle size of aluminum oxide is D50: 0.465 microns and D90: 1.213 microns.

[0054] Comparative Example 2

[0055] A method for preparing a slurry comprises: mixing the soybean meal activated carbon, pure water and a dispersant in Example 1, stirring the mixture in a double planetary mixer at a rotation speed of 2000 r / min and a revolution speed of 40 r / min for 20 min until the mixture is uniform, obtaining a solution A, mixing the solution A and an adhesive, stirring and ultrasonicating the mixture in a double planetary mixer having an ultrasonic oscillation function for 20 min under a vacuum environment until the mixture is uniform (the ultrasonic frequency of the ultrasonic wave is 5 kHz, the vacuum pressure is 0.06 KPA, the rotation speed of the stirring is 2000 r / min, and the revolution speed is 40 r / min), obtaining a slurry, wherein the adhesive is an acrylate copolymer solution, and the ratio of the soybean meal activated carbon, pure water, the acrylate copolymer in the adhesive to the dispersant is 30:64.5:5:0.5 by weight, the content of the acrylate copolymer in the acrylate copolymer solution is 20 wt% (the acrylate copolymer is polymerized from acrylic acid and acrylamide), and the dispersant is ammonium polyacrylate.

[0056] Examples 4 to 6 and Comparative Examples 3 to 4

[0057] A method for preparing a lithium battery separator comprises: placing a base film on a coating machine equipped with a slurry, coating the slurry on one side of the base film, pulling the base film into a drying device through a traction roller and drying it at 50° C. for Y min, obtaining a coating on the base film, and obtaining a lithium battery separator, wherein the coating speed is X m / min. The slurry is one of Examples 1 to 3 and Comparative Examples 1 to 2.

[0058] The X and Y values ​​are shown in Table 2.

[0059] Table 2

[0060]

[0061]

[0062] The parameters for preparing the lithium battery separator obtained in Example 4 are as follows:

[0063]

[0064] The parameters for preparing the lithium battery separator obtained in Example 5 are as follows:

[0065]

[0066]

[0067] The parameters for preparing the lithium battery separator obtained in Example 6 are as follows:

[0068]

[0069] The parameters of the lithium battery separator prepared in Comparative Example 3 are as follows:

[0070]

[0071] The parameters of the lithium battery separator prepared in Comparative Example 4 are as follows:

[0072]

[0073]

[0074] Figure 1 This is the SEM of the lithium battery separator prepared in Example 4.

[0075] Figure 2 This is the SEM of the lithium battery separator prepared in Comparative Example 3.

[0076] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A lithium battery separator, characterized in that: include: The base film and the coating on the base film include: modified soybean meal activated carbon, acrylate copolymer and dispersant. The ratio of modified soybean meal activated carbon, acrylate copolymer and dispersant is (30-40): (5-8): (0.2-0.5) by weight. The modified soybean meal activated carbon is soybean meal activated carbon with polar groups grafted on the surface, and the polar groups are amino groups.

2. The lithium battery separator according to claim 1, characterized in that: The method for obtaining the modified soybean meal activated carbon is: using a solution containing polyacrylamide to perform liquid phase modification on the soybean meal activated carbon at room temperature so that polar groups are grafted onto the surface of the soybean meal activated carbon, and the soybean meal activated carbon is carbonized soybean meal.

3. The lithium battery separator according to claim 1, characterized in that The dispersant is ammonium polyacrylate.

4. The lithium battery separator according to claim 1, characterized in that The particle size of the modified soybean meal activated carbon is: D50=0.2-0.3 μm, D90=0.5-0.8 μm, the porosity of the modified soybean meal activated carbon is 47-58%, and the specific surface area of ​​the modified soybean meal activated carbon is 2063-2400 m 2 / g.

5. The method for preparing a lithium battery separator according to any one of claims 1 to 4, characterized in that: The slurry is coated on a base film and dried to obtain a coating on the base film to obtain a lithium battery separator. The slurry includes: modified soybean meal activated carbon, acrylate copolymer and dispersant.

6. A slurry, characterized in that: include: Modified soybean meal activated carbon, water, adhesive and dispersant, wherein the adhesive is an acrylate copolymer solution, and the ratio of the modified soybean meal activated carbon, the water, the acrylate copolymer in the adhesive and the dispersant is (30-40): (60-70): (5-8): (0.2-0.5) by weight.

7. The slurry according to claim 6, characterized in that The content of the acrylate copolymer in the acrylate copolymer solution is 20-40 wt %.

8. A method for preparing the slurry according to any one of claims 6 to 7, comprising: The modified soybean meal activated carbon, water, adhesive and dispersant are mixed until uniform to obtain slurry.

9. Application of polyacrylamide and soybean meal activated carbon in synergistically improving the ionic conductivity and / or breakdown voltage of the separator.

10. The application of polyacrylamide and soybean meal activated carbon to synergistically improve the liquid absorption rate and / or liquid retention rate of diaphragms.